Hepatoprotective Activity of Phyllanthus lawii against Carbon Tetrachloride-induced hepatic damage in rats. - Chandrashekar, K S (International Journal of Pharmaceutical & Biological Archive, 2010)
The aerial parts of Phyllanthus lawii, family Euphorbiaceae was tested for hepatoprotective activity against CCl4 in rats. The ethanol extract of Phyllanthus lawii has shown significant activity, lowering the serum enzymes like SGOT and SGPT in rats intoxicated with CCl4. Phyllanthus lawii also reversed the histopathological change induced by CCl4, there by justifying the folk use of the plant.